Travelling wave simulations to the modified Zakharov-Kuzentsov model arising in plasma physics - Haci Mehmet Baskonus; Muzaffer Askin (Lviv Polytechnic Publishing House, 2016)
In this manuscript, we carry out the modified exp-(-Omega(xi))-expansion function method to the modified Zakharov-Kuzentsov equation with (2+ 1) dimensions arising in plasma physics. Then, the hyperbolic and complex travelling wave solutions are obtained to the model. It is observed that all results are verified to the model with the help of Wolfram Mathematica 9. We also plot the two- and threedimensional surfaces for all the travelling wave solutions obtained in this paper using the same computer program.
Keywords: The modified exp-(-Omega(xi))-expansion function method; the modified Zakharov-Kuzentsov equation; complex and hyperbolic function solution